PERAN MOTIVASI DAN DISIPLIN KERJA DALAM MENINGKATKAN KEPUASAN KERJA PERAWAT - Dwi Susanti; Husnul Khotimah; Maulidiyah Junnatul Azizah (Jurnal Keperawatan dan Kesehatan, 2026)
Background: Nurse job satisfaction is a critical indicator of healthcare service quality. Low job satisfaction can lead to decreased performance, increased absenteeism, and reduced quality of care. Work motivation and discipline are factors that may influence job satisfaction. Objective: This study aimed to analyze the relationship between work motivation and work discipline with nurse job satisfaction. Methods: This study employed a quantitative approach with a correlational design and cross-sectional method. The sample consisted of 80 nurses selected using total sampling. Data were collected through validated and reliable questionnaires. Data analysis was conducted using the Spearman Rank test due to non-normal data distribution. Results: The results showed a significant relationship between work motivation and job satisfaction (p=0.000; r=0.512), as well as between work discipline and job satisfaction (p=0.000; r=0.869). However, no significant relationship was found between work motivation and work discipline (p=0.785). Conclusion: Work motivation and discipline are important factors associated with nurse job satisfaction. Therefore, hospital management should improve human resource management strategies to enhance job satisfaction and healthcare service quality.